Basic and clinical research in oncology: is there background for a breakthrough? - N. V. Zhukov; S. A. Rumyantsev; S. A. Lukyanov (Онкогематология)
The appearance of anticancer drugs dramatically changed cancer treatment, allowing patients with a number of previously fatal diseases to achieve cure and prolong life in patients with incurable tumors. More than 100 anticancer drugs registered to date, many of which have beendeveloped in recent years using the latest advances in tumors molecular biology. At the same time the price of new anticancer drugs increasesmuch faster than efficacy of anticancer therapy. The situation is due largely to the fact that the current system of introduction of new anticancer drugs not performing initial tasks.